Evaluation of Epithelial Integrity with Various Transepithelial Corneal Cross-Linking Protocols for Treatment of Keratoconus. (12th August 2014) - Taneri, Suphi; Oehler, Saskia; Lytle, Grace; Dick, H. Burkhard
Abstract : Purpose . Corneal collagen cross-linking (CXL) has been demonstrated to stiffen cornea and halt progression of ectasia. The original protocol requires debridement of central corneal epithelium to facilitate diffusion of a riboflavin solution to stroma. Recently, transepithelial CXL has been proposed to reduce risk of complications associated with epithelial removal. Aim of the study is to evaluate the impact of various transepithelial riboflavin delivery protocols on corneal epithelium in regard to pain and epithelial integrity in the early postoperative period. Methods . One hundred and sixty six eyes of 104 subjects affected by progressive keratoconus underwent transepithelial CXL using 6 different riboflavin application protocols. Postoperatively, epithelial integrity was evaluated at slit lamp and patients were queried regarding their ocular pain level. Results . One eye had a corneal infection associated with an epithelial defect. No other adverse event including endothelial decompensation or endothelial damage was observed, except for epithelial damages. Incidence of epithelial defects varied from 0 to 63%. Incidence of reported pain varied from 0 to 83%. Conclusion . Different transepithelial cross-linking protocols have varying impacts on epithelial integrity. At present, it seems impossible to have sufficient riboflavin penetration without any epithelial disruption. A compromise between efficacy and epithelial integrity has to be found.